â€œCommentâ€ As A Development Of Marine Tourism And Flood Disaster Management Based On Go Green At Blendung Beach - M. Nur Khaqiqi; Luqman Haqiqi Amirulloh (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
The phenomenon of tidal waves in coastal areas is a common thing. The Keramat Sari beach is no exception (people are familiar with Blendung beach) which is located in Blendung Village, Ulujami District, Pemalang Regency. Around the Pantura, almost every year there are high and low tidal floods. This tidal flood even entered the houses of the residents. Rob at Blendung Beach has occurred since April until now (November), and reached the highest rob reaching an adult's foot on June 3, 2020. This tidal flood has greatly impacted the sustainability of Blendung Beach tourism in terms of the economy of the residents who manage and sell on Blendung Beach. Moreover, with the Covid-19 pandemic, which has made the economy decline so that the problem is even more complicated. Therefore, the author offers an idea in the form of